A predictive model of lymph node metastasis for thymic epithelial tumours. (11th April 2022) - Wang, Zi-Ming; Li, Feng; Sarigül, Lara; Nachira, Dania; Gonzalez-Rivas, Diego; Badakhshi, Harun; Rückert, Jens-C; Ng, Calvin S H; Ismail, Mahmoud
Abstract: OBJECTIVES: Thymic epithelial tumours (TETs) are relatively rare indolent malignancies in the mediastinum. Lymph node metastasis (LNM) is an important prognostic indicator for TETs; however, the pattern of LNM involved in TETs has yet to be elucidated. METHODS: Patients diagnosed with histologically confirmed thymoma (A–B3), thymic carcinomas and thymic neuroendocrine tumours, between 1988 and 2016 were identified from the Surveillance, Epidemiology, and End Results database. Univariable and multivariable logistic regression analyses were applied to identify the predictors for LNM. The predictive nomogram was built from the independent risk factors and measured using the concordance statistic. RESULTS: The overall proportion of TETs with LNM was 18.5% (200/1048). The rate of LNM in thymoma, thymic carcinomas and thymic neuroendocrine tumours was 6.8% (42/622), 30.2% (100/331) and 61.1% (58/95), respectively. According to the logistic regression analysis, histology type and T stage were independent factors correlated with LNM. A predictive nomogram model was developed with a concordance statistic of 0.807 (95% confidence interval: 0.773–0.841), which was significantly better than the T stage ( P < 0.001) while had limited benefit to the histology type ( P = 0.047). The calibration curve for the nomogram comparing the predicted and actual probabilities after bias correction showed good agreement. CONCLUSIONS: Nodal involvement was not uncommon in TETs. Main factors related to LNM in TETs were histology type and T stage. The probability of LNM could be well calculated using the predictive model. Abstract : The thymus is an important lymphoid organ that gradually deteriorates with the development of the adaptive immune system in childhood and is ultimately replaced by fat in adulthood [1].